Impact evaluation of a solar powered drip irrigation intervention in eastern Yemen - Jovanovic, Nina; Darwish, Maram; Kurdi, Sikandra; Yamauchi, Futoshi (International Food Policy Research Institute, 2025)
Groundwater irrigation supports agricultural production and local food security in arid regions, however costs and accessibility of fuel for pumping are a challenge in conflict-affected contexts. Solar-powered drip irrigation technology can support smallholder farmers in such settings. In this study we estimated the impacts of subsidized solar-powered drip irrigation systems on smallholder farmers’ production decisions and household food security via a clustered randomized control trial in eastern Yemen. We found that farmers in the treatment group were significantly less likely to cultivate cereals, more likely to cultivate horticultural crops, and more likely to sell a higher share of their harvests at market during the first season post‑intervention. These results provide causal evidence on the impact of solar drip irrigation systems on shifting smallholder farmers’ crop production toward higher-value crops. We did not find significant impacts on household food security within the short-term post-intervention period that the analysis covered. These findings also provide preliminary support for investments in solar and drip irrigation technology in Yemen, while acknowledging that more research is needed to address potential negative externalities.